Towards the integrated management of Water, Energy, Food, and Ecosystems (WEFE): A sensitization course for policy-/decision makers - Pandey, Vishnu Prasad; Rai, Rajesh Kumar; Koirala, Sanju; Bajracharya, Tri Ratna; Pokharel, Bharat Kumar; Onta, Nisha; Kattel, Rishi Ram; Dangol, Sabin; Khadka, Manohara; Elias, Marlene (2024)
Sustainable and integrated management of water, energy, food, and ecosystems requires a coordinated and cross-sectoral approach to manage trade-offs and maximize synergies among these deeply interconnected resources. This line of action is called the water-energy-food-ecosystem (WEFE) nexus approach. This 4-hour sensitization course is designed for policymakers and other high-level decisionmakers in any WEFE or WEFE-adjacent sector. It provides an overview of WEFE nexus concepts, issues, and approaches to foster integrated, equitable, and sustainable resource management at multiple scales. The course was co-developed under the umbrella of the CGIAR Initiative on NEXUS Gains by the Center for Water Resources Studies (CWRS), Institute of Engineering, Tribhuvan University, in partnership with the Alliance of Bioversity international and CIAT, and the International Water Management Institute (IWMI). It includes theory as well as practical applications and interactive elements.